Persistent problems and practices in information systems development: a study of mobile applications development and distribution. (27th March 2014) - Bergvall‐Kåreborn, Birgitta; Howcroft, Debra
Abstract The widespread uptake of mobile technologies has witnessed a re‐structuring of the mobile market with major shifts in the predominance of particular firms and the emergence of new business models. These sociotechnical trends are significant in the ways that they are influencing and shaping the working lives of software professionals. Building on prior research investigating the persistent problems and practices of systems development, this paper examines mobile applications development and distribution. A qualitative study of 60 developers based in Sweden, the UK and the USA was analysed around the interrelated problems of diversity, knowledge and structure. The analysis revealed how platform‐based development in an evolving mobile market represents significant changes at the business environment level. These changes ripple through and accentuate ongoing trends and developments, intensifying the persistent problems and challenges facing software developers.